2012
DOI: 10.2341/11-134-l
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ceramic Veneer Opacity and Exposure Time on the Polymerization Efficiency of Resin Cements

Abstract: The objective of this study was to determine the degree of conversion (DC), hardness (H), and modulus of elasticity (E) of a dual-cured resin cement, a light-cured resin cement, and a flowable resin cured through opaque or translucent ceramic with different exposure times. RelyX ARC (dual), RelyX Veneer (light-cured), and Filtek Z350 Flow resin specimens 0.5 mm thick were cured for 40, 80, and 120 seconds through 1-mm thick translucent or opaque feldspathic ceramic disks (n=10). The specimens were stored at 37… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
44
4
9

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(62 citation statements)
references
References 38 publications
5
44
4
9
Order By: Relevance
“…According to Meng et al, EM exhibited a strong correlation to the KHN for the dual‐cured resin cements evaluated. This data could explain the fact that EM and KHN were decreased continuously with the increase of ceramic thickness under dual‐cured cement and a light‐cured composite as well. In addition, in this study the self‐curing components of dual‐cured resin cements did not provide sufficient compensation when a thicker ceramic was used.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…According to Meng et al, EM exhibited a strong correlation to the KHN for the dual‐cured resin cements evaluated. This data could explain the fact that EM and KHN were decreased continuously with the increase of ceramic thickness under dual‐cured cement and a light‐cured composite as well. In addition, in this study the self‐curing components of dual‐cured resin cements did not provide sufficient compensation when a thicker ceramic was used.…”
Section: Discussionmentioning
confidence: 76%
“…Yet, the darker the ceramic, the more critical it is to achieve an optimal photopolymerization of the material . Studies observed lower resin cement microhardness values and degree of conversion, depending on the restoration shade tested . In fact, degree of conversion and hardness of composite materials can be associated with each other …”
mentioning
confidence: 99%
“…It was reported that the polymerization efficiency of dual-cure resins was affected by numerous factors: irradiation duration 24) , light intensity 25) , light transmission 26,27) , and ceramic shade 26) and thickness 28,29) . Specifically, a translucent ceramic which allowed more light to transmit through the material, as compared to an opaque ceramic, resulted in improved mechanical properties of dual-cure resin cement placed under the restorative material 30) .…”
Section: Vickers Hardness Of Resin Cement Placed Under Zr Restorationmentioning
confidence: 99%
“…In the present study, the use of 3-mm-thick ZR restorations could be deemed comparatively thick in consideration of the restoration thicknesses selected and employed in other studies 26,27,30) . Nonetheless, the high light intensity of the light curing unit (900 mW/cm 2 ) 25) , coupled with the high light transmission property of ZR 27) , enabled the polymerization of dual-cure resin cement placed under the ZR restoration.…”
Section: Vickers Hardness Of Resin Cement Placed Under Zr Restorationmentioning
confidence: 99%
“…The types of cements, adhesives and the treatment given to the tooth surface and ceramics are some of the most discussed topics in several studies. The adaptation of the lumineer on the tooth is also important to the success of the treatment [5].…”
Section: Introductionmentioning
confidence: 99%